On the Optimality of PAYG Pension Systems in an Endogenous Fertility Setting - G. Abío; Geraldine Mahieu; Cio Patxot (Center for Economic Studies and ifo Institute (CESifo), 2003)
In order to help in designing an accurate pension reform, we determine the resource allocation in an endogenous fertility model that generates an endogenous demographic transition by means of distinguishing between female and male labor. We analyze the problem of the optimal solution and characterize the decentralization of the first best. We show that a pension policy linking pension benefits to the number of children acts as a corrective tax system able to restore both the optimal capital stock and the optimal rate of population growth as a single instrument. We also show that neither a Beveridgean pension scheme nor a Bismarckian one can decentralize the first best.
Keywords: 330; demographic transition; endogenous fertility; pay-as-you-go pension system; golden rule